2017
DOI: 10.2147/copd.s139035
|View full text |Cite
|
Sign up to set email alerts
|

Severe exacerbation and pneumonia in COPD patients treated with fixed combinations of inhaled corticosteroid and long-acting beta2 agonist

Abstract: BackgroundIt remains unclear whether severe exacerbation and pneumonia of COPD differs between patients treated with budesonide/formoterol and those treated with fluticasone/salmeterol. Therefore, we conducted a comparative study of those who used budesonide/formoterol and those treated with fluticasone/salmeterol for COPD.MethodsSubjects in this population-based cohort study comprised patients with COPD who were treated with a fixed combination of budesonide/formoterol or fluticasone/salmeterol. All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…This could be related to the low proportion of patients using fluticasone propionate, since previous data suggests its use is associated with a particular increase in the risk of pneumonia. For example, a population-based cohort study showed that patients receiving fluticasone had a higher incidence rate and a higher risk of pneumonia than patients receiving budesonide (12.11 per 100 person-years vs. 10.65 per 100 person-years, adjusted HR 1.13, 95% CI: 1.08–1.20) [ 27 ]. An observational study also showed that the rate of serious pneumonia was doubled with fluticasone propionate (rate ratio [RR] 2.01; 95% CI: 1.93–2.10) and increased with the daily dose.…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to the low proportion of patients using fluticasone propionate, since previous data suggests its use is associated with a particular increase in the risk of pneumonia. For example, a population-based cohort study showed that patients receiving fluticasone had a higher incidence rate and a higher risk of pneumonia than patients receiving budesonide (12.11 per 100 person-years vs. 10.65 per 100 person-years, adjusted HR 1.13, 95% CI: 1.08–1.20) [ 27 ]. An observational study also showed that the rate of serious pneumonia was doubled with fluticasone propionate (rate ratio [RR] 2.01; 95% CI: 1.93–2.10) and increased with the daily dose.…”
Section: Discussionmentioning
confidence: 99%
“…This study used a subset of the NHIRD comprising information on individuals with COPD. 5 , 7 There were 62,505 eligible COPD patients who were aged older than 40 years between 2000 and 2005. We excluded 40,026 patients who did not meet the following criteria: 1) patients without prescription of ACEi or ARB before COPD index date; 2) patients who received ACEi or ARB <90 days after COPD index date; 3) patients with ACEi and ARB combined treatment; and 4) patients who died or were diagnosed with pneumonia or severe pneumonia prior to being indexed ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The patients with pneumonia were identified according to the International Classification of Diseases, Ninth Revision, Clinical Modification codes as previously described. 5 , 17 For patients with more than one episode of pneumonia, only the first episode was included. A severe exacerbation was defined as a COPD-related hospitalization or emergency department visit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify patients with COPD, all NHI enrollees who were 40 years or older and had a diagnosis of COPD (ICD-9-CM codes 491, 492, and 496) in at least two outpatient (OPD) visits or one hospitalization were screened. 12 , 13 The index date was defined as the date of first medical visit with the ICD-9 CM code for COPD. Those screened patients who had received short-acting muscarinic antagonist (SAMA), long-acting muscarinic antagonist (LAMA), short-acting β2-agonist (SABA), long-acting β2-agonist (LABA), inhaled corticosteroid (ICS), fixed-dose combination of LABA and ICS, or xanthines after the index date were enrolled in this study.…”
Section: Methodsmentioning
confidence: 99%